Accelerated Age-Dependent Hippocampal Volume Loss in Parkinson Disease With Mild Cognitive Impairment. (September 2017) - Schneider, Christine B.; Donix, Markus; Linse, Katharina; Werner, Annett; Fauser, Mareike; Klingelhoefer, Lisa; Löhle, Matthias; von Kummer, Rüdiger; Reichmann, Heinz; ,; Storch, Alexander
Background: Patients with Parkinson disease are at high risk of developing dementia. During the course of the disease, a substantial number of patients will experience a cognitive decline, indicating the dynamics of the underlying neuropathology. Magnetic resonance imaging (MRI) has become increasingly useful for identifying structural characteristics in radiological brain anatomy existing prior to clinical symptoms. Whether these changes reflect pathology, whether they are aging related, or both often remains unclear. We hypothesized that aging-associated brain structural changes would be more pronounced in the hippocampal region among patients with Parkinson disease having mild cognitive deficits relative to cognitively unimpaired patients. Methods: Using MRI, we investigated 30 cognitively healthy patients with Parkinson disease and 33 patients with nondemented Parkinson disease having mild cognitive impairment. All participants underwent structural MRI scanning and extensive clinical and neuropsychological assessments. Results: Irrespective of the study participants' cognitive status, older age was associated with reduced cortical thickness in various neocortical regions. Having mild cognitive impairment was not associated with an increased rate of cortical thinning or volume loss in these regions, except in the hippocampus bilaterally. Conclusion: Patients with Parkinson disease having mild cognitive impairment show an accelerated age-dependent hippocampal volume loss when compared with cognitively healthy patients with Parkinson disease. This may indicate pathological processes in a key region for memory functioning in patients with Parkinson disease at risk of developing dementia. Structural MRI of the hippocampal region could potentially contribute to identifying patients who should receive early treatment aimed at delaying the clinical onset of dementia.